Mediation Analysis, Moderation of Digital Transformation and Fintech Adoption and the Role of Financial Literacy in Improving Sustainable Performance - Yahsyallah; Ronny Malavia Mardani; Nurhidayah (LP2M IAIN Palopo, 2025)
The banking industry is currently in an era of rapid transformation, driven by advances in digital technology and innovation in the financial sector. These changes create opportunities and challenges for banks in maintaining competitiveness and improving sustainable performance. This study aims to explore how increasing financial literacy can strategically influence the relationship between digital transformation, Fintech adoption, and competitive sustainability. The type of research used in this study is quantitative. The population in this study consists of employees of Bank BSI under the Malang Area Office. Using a simple random sampling technique. To measure the sample size to be studied, the researcher used the Slovin formula. Data analysis used Structural Equation Modeling, Partial Least Square (SEM PLS) techniques. The results of the study show that digital transformation has a positive effect on sustainable performance. Digital Transformation has a positive effect on fintech adoption. Fintech adoption has a positive effect on sustainable performance. The results also show that fintech adoption significantly mediates the relationship between digital transformation and sustainable performance. Digital transformation, financial literacy on fintech adoption shows a significant moderating effect. This can be explained that individuals with high financial literacy tend to be more selective in adopting new technology.